2019
DOI: 10.3389/fncom.2019.00077
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Band Resonance and Intrinsic Oscillations in a Biophysically Detailed Model of the Subthalamic Nucleus-Globus Pallidus Network

Abstract: Increased beta-band oscillatory activity in the basal ganglia network is associated with Parkinsonian motor symptoms and is suppressed with medication and deep brain stimulation (DBS). The origins of the beta-band oscillations, however, remains unclear with both intrinsic oscillations arising within the subthalamic nucleus (STN)—external globus pallidus (GPe) network and exogenous beta-activity, originating outside the network, proposed as potential sources of the pathological activity. The aim of this study w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 113 publications
(201 reference statements)
2
22
0
Order By: Relevance
“…Increasing the strength of the hyperdirect pathway led to increased resonance in the model and also to a widening of the frequency bands where resonance was observed ( Figure 3B). This observed resonance is consistent with other modeling investigations of the STN-GPe network, where firing-rate models (Nevado-Holgado et al, 2014;Detorakis and Chaillet, 2017;Liu et al, 2017Liu et al, , 2020 and conductancebased neuron models (Ahn et al, 2016;Shouno et al, 2017;Koelman and Lowery, 2019) were used to investigate the behavior of STN-GPe network in response to external drives. Although those studies have illustrated the resonant capabilities of the STN-GPe network of both firing-rate and conductance-based models separately, this study is the first to demonstrate that both modeling approaches lead to comparable results (Figure 3).…”
Section: Endogenous and Exogenous Generation Of Oscillationssupporting
confidence: 89%
“…Increasing the strength of the hyperdirect pathway led to increased resonance in the model and also to a widening of the frequency bands where resonance was observed ( Figure 3B). This observed resonance is consistent with other modeling investigations of the STN-GPe network, where firing-rate models (Nevado-Holgado et al, 2014;Detorakis and Chaillet, 2017;Liu et al, 2017Liu et al, , 2020 and conductancebased neuron models (Ahn et al, 2016;Shouno et al, 2017;Koelman and Lowery, 2019) were used to investigate the behavior of STN-GPe network in response to external drives. Although those studies have illustrated the resonant capabilities of the STN-GPe network of both firing-rate and conductance-based models separately, this study is the first to demonstrate that both modeling approaches lead to comparable results (Figure 3).…”
Section: Endogenous and Exogenous Generation Of Oscillationssupporting
confidence: 89%
“…As the primary focus of this study, however, was not the role of the striatum in the generation of network pathological oscillations, its contribution to the network was simplified. A recent study investigating the role of exogenous cortical and striatal beta inputs to the STN-GPe network using detailed multi-compartment models of STN and GPe showed that resonant beta-band oscillatory activity within the STN-GPe loop becomes phase-locked to exogenous cortical beta inputs and that this behavior can be further promoted by striatal input to the loop with the correct phase (Koelman and Lowery, 2019). The network presented here captures the exogenous cortical patterning of the STN-GPe loop but omits possible further amplification of the beta-band oscillatory activity due to the striatum.…”
Section: Limitationsmentioning
confidence: 99%
“…Currently, increasing amounts of LFP data are obtained from patients with various brain disorders and in related animal models, such as AD and PD. Among these diseases, LFP recording and analysis play a key role in decoding PD, and levodopa and DBS have been widely used to modulate beta oscillations in PD patients and to treat PD symptoms [7][8][9][10]. However, commercial implantable recording electrodes are expensive and one-off in recording LFPs in freely moving animals, forcing more and more neuroscientists to prepare an implantable electrode by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Among these brain disorders, numerous LFP data were recorded from the PD patient and animal model to decode its brain circuit. It has been found that the beta-band oscillations are consistently strengthened with dopamine loss both in PD patients and parkinsonian animal models, while levodopa and deep brain stimulation (DBS) have been witnessed to improve PD symptoms and decrease the beta oscillations [7][8][9][10]. Thus, a good recording electrode will be a powerful tool to investigate LFPs and reveal the mechanisms underlying brain disorders.…”
Section: Introductionmentioning
confidence: 99%